2012
DOI: 10.2460/ajvr.73.8.1119
|View full text |Cite
|
Sign up to set email alerts
|

Sectional anatomic and magnetic resonance imaging features of the head of juvenile loggerhead sea turtles (Caretta caretta)

Abstract: The MRI images obtained through this study provided valid information on anatomic characteristics of the head in juvenile loggerhead sea turtles and should be useful for guiding clinical evaluation of this anatomic region in this species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…Afterwards, we selected those anatomic sections that better matched the CT and MRI images to identify the relevant structures of the rhinoceros iguana head. To help in this process, we also used anatomical texts and relevant references describing this species [ 4 , 21 , 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Afterwards, we selected those anatomic sections that better matched the CT and MRI images to identify the relevant structures of the rhinoceros iguana head. To help in this process, we also used anatomical texts and relevant references describing this species [ 4 , 21 , 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Transverse ultrasonographic image of the brain in a leopard gecko . Note the gel layer above the skull, necessary to obtain this ultrasonographic image.…”
Section: Resultsmentioning
confidence: 99%
“…However, due to the wide interval between slices employed in this study, some of these structures were not clearly discernible in the transverse MR views. Comparable investigations conducted in other exotic species, such as rabbits, guinea pigs, iguanas, and loggerhead turtles, have consistently demonstrated that this combination is essential to comparing the relative positions and sizes of cephalic or other anatomical structures [ 3 , 14 , 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, excellent discrimination of the main components of the encephalon , including the rhinencephalon , telencephalon , diencephalon , mesencephalon , metencephalon , and myelencephalon , was achieved with the T2W images. These images have proven to be useful for anatomical and clinical studies of various exotic species [ 3 , 12 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. Therefore, the transverse T2W images revealed the olfactory bulb and its recess, which was hyperattenuated compared to the telencephalon .…”
Section: Discussionmentioning
confidence: 99%